FOOD INDUSTRY IN UKRAINE: CURRENT STATE, TRENDS AND PROSPECTS OF DEVELOPMENT (INNOVATIVE ECONOMY, 2020)
Hrynchutskyi V.I., Blashchak B.Ya. FOOD INDUSTRY IN UKRAINE: CURRENT STATE, TRENDS AND PROSPECTS OF DEVELOPMENTPurpose. The aim of the article is the investigation of the state, trends and prospects of food industry development in Ukraine and substantiation of directions of its strategic development.Methodology of research. General scientific and special methods are used in the process of research for the analysis of the state and trends of the food industry, in particular: a systematic approach and methods of statistical, economic and mathematical analysis.Findings. The state of the food industry and the main tendencies of its development are investigated and 20 main types of products, which are the most demanded by the market, are distinguished. It has been determined that there are several branches of the food industry’s powerful drivers that are directly related to the production of the main export-oriented products, namely: oils and animal fats, cocoa, chocolate and sugar confectionery.The statistical data on volumes of production and sales of products are studied and the main sub-sectors of the food industry are distinguished, in which the growth rates of production volumes are observed.The average indices of food production have been substantiated and conclusions have been formed, which testify to stabilization of the situation in the industry and restoration of its economic growth in comparison with the negative tendencies of the previous years. Food products are ranked according to their growth rates relative to the previous period.It is noted that domestic enterprises have significant achievements in export activity. The regions with the largest increase in the volume of production of food products are determined. It has been established that a large number of enterprises of various sizes and forms of ownership that compete among themselves in the regional markets operates in the food industry market.Originality. The strategic opportunities of the food industry of Ukraine are substantiated on the basis of modernization of production, increase of volumes of production and entering new international markets.Practical value. The results of the study can be used in the practical activities of food industry enterprises.Key words: food industry; production; demand; production; export; sales; competitiveness.
Keywords: Key words; food industry; production; demand; export; sales; competitiveness.